Trivalvular infective endocarditis secondary to Granulicatella adiacens and Peptostreptococcus spp. (2019) - Verdecia, Jorge; Vahdat, Kelia; Isache, Carmen
Abstract: We present a case of a 42-year-old Caucasian man that came to our facility complaining of dyspnea and subjective fevers and was found to have infective endocarditis. His blood cultures initially grew Peptostreptococcus spp and he was started on penicillin and gentamicin. Repeat blood cultures, drawn 48 h later, became positive for Granulicatella adiacens . Vancomycin was added at this point, given reports of growing penicillin resistance of Granulicatella spp . Transthoracic echocardiogram showed multiple vegetations on the aortic, mitral and tricuspid valves. The patient's final antibacterial regimen consisted of intravenous penicillin G 24 million units daily and vancomycin (goal trough of 15–20) for a total of 6 weeks. The first 2 weeks of his regimen also included gentamicin. The patient was not considered for valve replacement surgery given concern for continued use of illicit intravenous drugs. Peptostreptococcus species are anaerobic, non-spore forming, gram-positive cocci, thought to generally have a subacute clinical presentation. Granulicatella genus is nutritionally deficient bacteria which require a supplemented media in order to grow. Both of these bacteria are present in the mouth and gastrointestinal flora. The rate of infective endocarditis from anaerobic species has been reported up to 16%, which includes multiple species. While on nutritionally deficient bacteria are reported to be involved on infective endocarditis in the range of 3–8%. Antimicrobial resistance is on the rise for both of these species, which makes the appropriate choice of antimicrobials quite important.